Health of parents of individuals with developmental disorders or mental health problems: Impacts of stigma. (November 2018) - Song, Jieun; Mailick, Marsha R.; Greenberg, Jan S.
Abstract: Objective: Parents of individuals with developmental disorders or mental health problems often provide life-long care and support to their children, which negatively affects their health in part due to chronic stress. This study aimed to examine the experience of stigma as a source of chronic stress among parents of individuals with developmental disorders or mental health problems and the effect of stigma on parental health outcomes. Method: Using data from the Survey of Midlife in the United States (MIDUS 2 and 3), we constructed a sample for a longitudinal analysis including 128 parents of individuals with developmental disorders (e.g., autism, cerebral palsy, epilepsy, Down syndrome, intellectual disabilities, brain injury, ADD/ADHD) or mental health problems (e.g., bipolar disorder, schizophrenia, major depression) and 2256 parents whose children were nondisabled. Results: Parents who had children with developmental disorders or mental health problems prior to the beginning of the study (i.e., at MIDUS 1) reported higher levels of stigma related to embarrassment/shame and daily discrimination than parents of nondisabled individuals ten years later at MIDUS 2, which in turn were associated with poorer parental health outcomes (poorer self-rated health and a greater number of chronic conditions) nearly a decade after that at MIDUS 3. Conclusions: The findings suggest that the stigma associated with parenting a child with disabilities may be one mechanism that places such parents at risk for poor health. Efforts to alleviate the stigma associated with developmental disorders or mental health problems may have beneficial effects on health of parents of individuals with such conditions. Highlights: Parents of children with disabilities experience a higher level of stigma. A higher level of parental stigma is associated with poorer health 10 years later. Policies aimed at destigmatizing disabilities would have public health benefits.